Tropaeolin OO as a Chemical Sensor for a Trace Amount of Pd(II) Ions Determination - Adrianna Pach; Agnieszka Podborska; Edit Csapo; Magdalena Luty-Błocho (Molecules, 2022)
The selective determination of metals in waste solutions is a very important aspect of the industry and environmental protection. Knowledge of the contents and composition of the waste can contribute to design an efficient process separation and recovery of valuable metals. The problematic issue is primarily the correct determination of metals with similar properties such as palladium and platinum. Thus this paper focuses on the development of a selective method that enables Pd(II) determination in the presence of Pt(IV) ions using the azo-dye tropaeolin OO (TR). For this purpose, the process of the metalorganic complex formation and Pd(II) ions determination were studied by using UV–Vis spectrophotometry under different conditions: solvents (water and B-R buffer), pH (2.09–6.09), temperature (20–60 °C), anions and cations concentrations. The formed metalorganic complex between Pd and tropaeolin OO allows for distinguishing Pd(II) ions from both platinum complexes, i.e. Pt(II), Pt(IV). Moreover, the proposed method can be applied to solutions containing both chloride and chlorate ions. The obtained characteristic spectrum with two maxima allows the determination of palladium even in the presence of other cations (Na, K, Mg, Zn, Co, Ni, Al) and changed concentrations of Pt(IV) ions. Furthermore, the developed spectrophotometric method for the Pd(II) ions determination using tropaeolin OO is characterized by high selectivity towards palladium ions.